Enhancing Writing Ability of The Seventh Grade In SMP Negeri 3 Parepare Through Guided Inquiry Method - Ayunitasari, Ayunitasari; Patahuddin, Patahuddin (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
The result research of students in grade VII.4 of SMP Negeri 3 Parepare showed that student learning outcomes were still relatively low, namely that the learning completeness score only reached, which had not achieved DEPDIKNAS 2015 standards of 75. This research used quasi-experimental design with two groups namely pre-test and post-test. The population of this research was the seventh grade students of SMP Negeri 3 Parepare of gazal semeste in academic year 2017/2018 with sample taking technique which was clustering random sampling consisting of 58 students from two classes taken from the seventh grade population, where class VII.4 is an experimental class and VII.5 as a control class. The results showed that the learning process using guided inquiry method could improve students' writing ability, based on the results of the research in Chapter IV it was known that the average score of learning outcomes before applying guided inquiry method or giving a pre-test was 60.00 from the DEPDIKNAS 2015 standard score with the learning outcomes category in the low category. After applying the guided inquiry method, the researcher obtained the results of the average score of students in the post-test was 79.82. Based on data analysis through the test formula shows the final t-test (6.39) was higher than the value of t-table (2.000). This showed that H0 is rejected and H1 is accepted, students who are taught to use guided inquiry methods are more effective than guided discovery methods.